Gangs and organized crime - Knox, George W. (Routledge, 2019)
chapter 1 -Gang and Organized Crime History and Foundations -- chapter 2 -Los Angeles Area Street Gangs -- chapter 3 -Chicago Area Street Gangs -- chapter 4 -Outlaw Motorcycle Gangs (OMGs) -- chapter 5 -Prison Gangs -- chapter 6 -Females in the Gang World -- chapter 7 -Gangs and Violence -- chapter 8 -Gangs and the Military -- chapter 9 -Asian, East Asian, and African Organized Crime -- chapter 10 -Italian Organized Crime -- chapter 11 -Russian and Other European Organized Crime -- chapter 12 - Drug and Other Trafficking Organizations in the Americas -- chapter 13 - Investigation and Prosecution of Gangs and Organized Crime Groups.